LIMB-SHAKING SEBAGAI MANIFESTASI YANG JARANG DARI TRANSIENT ISCHEMIC ATTACK AKIBAT STENOSIS BERAT ARTERI KAROTIS - Tini, Kumara (PERDOSNI, 2018)
Ã‚Â Ã‚Â LIMB-SHAKING AS A RARE MANIFESTATION OF TRANSIENT ISCHEMIC ATTACK ASSOCIATED WITH SEVERE CAROTID ARTERI STENOSISABSTRACTLimb-shaking is a rare manifestation of Transient Ischemic Attack (TIA), commonly occurs when a severe carotid stenosis causes a cerebral hypoperfusion. Male 53 years of age experienced repeated limb-shaking within a week of left hand and arm accompanied by a vision of light sparks. Brain Magnetic Resonance Imaging (MRI) and Magentic Resonace Angiography (MRA) showed chronic watershed infarct at right fronto-parietal lobes and 80-90% severe stenosis of right internal carotid artery with digital subtraction angiography (DSA) showed 70% stenosis at the same site. Carotid Artery and Stenting (CAS) was done a week after and symptoms disappeared subsequently. Recognizing this rare symptom of severe carotid stenosis is very important since appropriate management can minimized the risk of future stroke.Keyword:Ã‚Â Carotid stenosis, Limb-shaking, TIAABSTRAKLimb-shakingÃ‚Â adalah manifestasi yang jarang dariÃ‚Â transient ischemic attackÃ‚Â (TIA), biasanya terjadi akibat hipoperfusi serebri pada stenosis berat arteri karotis. Laki-laki 53 tahun mengalamiÃ‚Â limb-shakingÃ‚Â berulang dalam seminggu pada lengan dan tangan kiri disertai melihat percikan sinar.Ã‚Â Magnetic resonance imagingÃ‚Â (MRI) danÃ‚Â magnetic resonance agiographyÃ‚Â (MRA) kepala menunjukkan infark di areaÃ‚Â watershedÃ‚Â lobus fronto-parietal kanan dan stenosis 80-90% di arteri karotis interna kanan, sertaÃ‚Â digital substraction angiographyÃ‚Â (DSA) menunjukkan stenosis 70% pada lokasi yang sama. Keluhan hilang setelah pasien dilakukan tindakan revaskularisasiÃ‚Â carotid artery and stentingÃ‚Â (CAS) seminggu kemudian. Pengenalan gejala yang jarang dari stenosis berat arteri karotis ini sangat penting, karena dengan penanganan yang tepat dapat mengurangi terjadinya stroke.Kata kunci:Ã‚Â Ã‚Â Limb-shaking, stenosis karotis, TIAÃ‚Â